Economic burden of cardiovascular diseases in the enlarged European Union. - Leal, J; Luengo-Fernández, R; Gray, A; Petersen, S; Rayner, M (2006)
AIMS: Cardiovascular disease (CVD), together with its main components, coronary heart disease (CHD), and cerebrovascular diseases, is the main source of morbidity and mortality in the European Union (EU), but to date, there has not been any systematic cost-of-illness study to assess the economic impact of CVD in the EU. METHODS AND RESULTS: CVD-related expenditure was estimated using aggregate data on morbidity, mortality, and healthcare resource use. Healthcare costs were estimated from expenditure on primary, outpatient, emergency, and inpatient care, as well as medications. Costs of unpaid care and lost earnings due to morbidity and premature death were included in the study. CVD was estimated to cost the EU Euro 169 billion annually, with healthcare accounting for 62% of costs. Productivity losses and informal care represented 21% and 17% of costs, respectively. CHD represented 27% and cerebrovascular diseases 20% of overall CVD costs. CONCLUSION: CVD is a leading public health problem. Our study is the first to assess the economic burden of CVD across the EU, and our results should help policy makers evaluate policy impact and prioritize research expenditures. However, because of data unavailability, our study has important limitations, which highlight the need for more accurate and comparable CVD-specific information.